2019
DOI: 10.1016/j.mce.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of 17β-hydroxysteroid dehydrogenase type 1, 2 and 14: Structures, biological activities and future challenges

Abstract: During the past 25 years, the modulation of estrogen action by inhibition of 17β-hydroxysteroid dehydrogenase types 1 and 2 (17β-HSD1 and 17β-HSD2), respectively, has been pursued intensively. In the search for novel treatment options for estrogen-dependent diseases (EDD) and in order to explore estrogenic signaling pathways, a large number of steroidal and nonsteroidal inhibitors of these enzymes has been described in the literature. The present review gives a survey on the development of inhibitor classes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 112 publications
1
35
0
Order By: Relevance
“…Other pathways proteins. 17β-HSD2 is a microsomal enzyme that catalyzes the oxidation of sex steroids testosterone and estradiol (E2) to less active ketones androstenedione and estrone (E1) 85,86 . It is reported that the inhibition of 17β-HSD2 in a in vivo monkey model and osteoporosis patients is beneficial to increase in E2 and testosterone levels that facilitate reduction in bone resorption and maintenance of bone formation 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Other pathways proteins. 17β-HSD2 is a microsomal enzyme that catalyzes the oxidation of sex steroids testosterone and estradiol (E2) to less active ketones androstenedione and estrone (E1) 85,86 . It is reported that the inhibition of 17β-HSD2 in a in vivo monkey model and osteoporosis patients is beneficial to increase in E2 and testosterone levels that facilitate reduction in bone resorption and maintenance of bone formation 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies also established that 17β-HSD1 accomplished complex processes in ligand binding sites 11 , 28 . That is, the enzyme protein could change its conformation depending on the inhibitor molecule offered 12 .…”
Section: Resultsmentioning
confidence: 89%
“…These mechanisms indicate that a very small change in inhibitor structure can make large differences in the course of binding to the enzyme 12 . Inhibitor studies, therefore, may give ambiguous picture with regard to the binding properties of the compounds and complete structure–activity relations could be revealed sometimes scarcely 9 , 11 , 12 .…”
Section: Resultsmentioning
confidence: 99%
“…T here are studies which indicate that breast cancer is one of the main health problems worldwide [1][2][3][4]. It is noteworthy that some drugs have been used to treatment of breast cancer such as tamoxifen (estrogen-receptor antagonist) [5], anastrozole, letrozole or exemestane (aromatase inhibitors) [6][7][8], fisetin or methyl paraben (17-hydroxy dehydrogenase type 1 inhibitors) [9,10]; however, some of these drugs may produce some adverse effects such as secondary endometrial cancer [11] and bone loss [12]. In the search of new pharmacological treatment to breast cancer, some drugs have been developed; for example, the asymmetric synthesis of a piperidine derivative via an organocatalytic Michael-Henry reaction with biological activity against breast cancer in vitro [13].…”
Section: Introductionmentioning
confidence: 99%